Brand Equity in Prescription Drugs:A Study Of Malaysian Customer Perception towards Prescription Drugs Branding Based on Brand Equity Concept - Tham, Lin Hui (2005)
When brand equity became a hot topic in the late 80’s, the success of one industry after another shows that it has a prominent role in the realm of marketing. According to David Aaker, brand equity can be categorised into brand awareness, brand associations, perceived quality, brand loyalty and other proprietary brand assets. The brand equity brings values to both customer and firms. Brand equity, however, cannot be measured in dollars and cents but rather a direct result of how consumers value a brand based on their experiences and perceptions. Therefore, Kevin Keller’s model examines brand equity based on customer perception. In the Malaysian pharmaceutical industry, prescription brands are mainly from innovator companies. However, the innovator brands are not as compelling as the FMCG’s due to the support for generic medications. There are two types of buyers, business-to-business and business-to-consumer buyers. The doctors and pharmacists are the business customers with a unique role where they have deep influence in consumer decision to purchase. Therefore, the first part of the study is to understand the perceptions of both business customers and consumers towards Aaker’s five brand assets. The fifth brand asset selected is country-of-origin because it is assumed that developed country is preferred to developing country when purchasing prescription drugs. In addition, in the second part of the study, the researcher is interested to find out the roles of corporate and condition brands in prescription branding based on customers’ feedback. The information gathered provides preliminary understandings of the effects of the pharmaceutical companies’ branding and marketing strategies in Malaysian markets. Findings from this study demonstrate that the innovator brands are strong in perceived quality and performance-related associations. Brand awareness, imagery-related associations, brand loyalty and country-of-origin are viewed as less important. The B2B buyers are the technical buyers who place performance as the most important factors in their purchase decision. The B2C buyers consider doctor’s recommendations as the most important factor. The B2C market is divided into brand onscious and brand indifferent segments. The brand equity is weak in the prescription market due to the constraints of healthcare regulations and the unpleasant connotation of disease and treatment. The results also show that corporate branding has a positive role in prescription drugs and condition branding is generally not favoured for common conditions. In conclusion, brand equity can be created and maintained if pharmaceutical companies are able to find ways to communicate their brand to their customers, particularly the B2B buyers and brand-conscious consumers. Although this can be difficult, given the regulation and business constraints, it is still possible to build a strong brand. This is largely dependent on the ability of pharmaceutical companies to successfully implement their marketing mix to uncover brand promise that delivers product satisfaction and improved ‘quality of life’.